2022
DOI: 10.1136/bmjopen-2021-056043
|View full text |Cite
|
Sign up to set email alerts
|

LobE-Specific lymph node diSsectiON for clinical early-stage non-small cell lung cancer: protocol for a randomised controlled trial (the LESSON trial)

Abstract: IntroductionLung cancer was the most common malignancy and the leading cause of cancer-related death in China or worldwide, and surgery is still the preferred treatment for early-stage non-small cell lung cancer (NSCLC). The pattern of lymph node metastasis was found potentially lobe specific, and thus, lobe-specific lymph node dissection (L-SLND) was proposed to be an alternative to systematic lymph node dissection (SLND) for the treatment of early-stage NSCLC.Methods and analysisThe LobE-Specific lymph node … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…With this, they suggested that lymph node dissection may not be required for pure GGOs and some part-solid GGOs. In contrast to the preceding two reviews, they also acknowledged that considering this excellent prognosis of GGOs, along with the intricacy of conducting RCTs, which demand excessive sampling and follow-up time, RCTs may not be imperative to determine the optimal lymphadenectomy strategy for GGOs, although studies are needed to understand lymphadenectomy for NSCLC in general [ 71 ]. Currently, two ongoing trials are assessing approaches to lymph node removal in GGOs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With this, they suggested that lymph node dissection may not be required for pure GGOs and some part-solid GGOs. In contrast to the preceding two reviews, they also acknowledged that considering this excellent prognosis of GGOs, along with the intricacy of conducting RCTs, which demand excessive sampling and follow-up time, RCTs may not be imperative to determine the optimal lymphadenectomy strategy for GGOs, although studies are needed to understand lymphadenectomy for NSCLC in general [ 71 ]. Currently, two ongoing trials are assessing approaches to lymph node removal in GGOs.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, two ongoing trials are assessing approaches to lymph node removal in GGOs. The LESSON trial is an ongoing, single-institutional, randomized, double-blind, and parallel-controlled trial in China aiming to assess lymph node dissection in clinically diagnosed stage IA NSCLC with GGO components ≥50% (i.e., CTR ≤ 0.5) [ 71 ]. The MELDSIG trial is another ongoing multi-institutional randomized trial in China, analyzing the difference between dissection and sampling in stage Ia NSCLC with GGOs [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, LS-LND could be a reasonable surgical strategy compared with S-LND for the treatment of some patients with NSCLC, and its clinical benefits regarding postoperative complications and OS need to be considered. Further RCTs, including a recent study 42 and JCOG 1413, 10 could provide guidance on practicing LS-LND and clarify its impact in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, 2 ongoing trials are assessing approaches to lymph node removal in GGOs. The LESSON trial is an ongoing, single-institutional, randomized, double-blind, and parallel-controlled trial in China aiming to assess lymph node dissection in clinically diagnosed stage IA NSCLC with GGO components ≥50% (i.e., CTR ≤ 0.5) [69]. The MELDSIG trial is another ongoing multi-institutional randomized trial in China, analyzing the difference between dissection and sampling in stage Ia NSCLC with GGOs [70].…”
Section: Is Sublobar Resection Superior To Lobectomy For Ggos?mentioning
confidence: 99%